Pengaruh Biopolimer Pada Stabilitas Lereng Swelling soil - Dewi Amalia; Bagus Guritno; Hendry Hendry; Geni Firuliadhim (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2021)
Many studies have begun to develop the concept of cracked soil. The results of research related to cracked soil are able to answer the irregularities that occur, such as the difference in the results of the stability analysis which is considered safe with the conventional bishop method, while the conditions in the field are landslides. Swelling soil is soil that is susceptible to changes in water content. This type of soil is very prone to cracking. To build infrastructure on the swelling soil type, an improvement must be made, one of which is by mixing the swelling soil with biopolymer. The results of this biopolymer mixing are then modeled in the New Slope Stability Analysis Program (NSSAP) 1.0 which refers to the concept of cracked soil. From the analysis, it was found that the slope safety factor before improvement with biopolymer was 0.305 and the safety factor after improvement with biopolymer was 2.006. From the results of this study, it can be seen that the role of biopolymers in stabilizing swelling soil is quite large, which is around 558%.